Reflective jacket - Harun, Siti Nur Idayu; Enizam, Shasha Umairah; Othman, Siti Amira (Penerbit UTHM, 2020)
Safety product is created for workers, students, people and society to prevent from dangerous, harmful, injured also risks situation that can be occurs before, during and after works. The materials to produce the safety product must be strong, hard, good resistance, fast treatment and others characteristic that can be protect and prevent the user from the dangerous. Sometimes, the cost to produce the safety product is expensive because of the material to make the safety product become the good products.